Enhancing the durability of filtration the ultrafine aerosol by electrospun polymer filter containing quaternary ammonium moiety - Lee, Su-Bin; Cho, Hee-Joo; Ha, Yu-Mi; Kim, Seo-Jeong; Chung, Byung-Joo; Son, Won Keun; Kang, Kyung Seok; Jung, Yong Chae; Park, Kihong; Lee, Jae-Suk (ELSEVIER SCI LTD, 2017)
Functionalized polymer filter (FPF) was fabricated using a synthesized terpolymer containing a quaternary ammonium moiety via electrospinning method to enhance the durability of air filters. Removal efficiency and durability of FPF were exhibited compared with those of polystyrene (PS) filter and a commercial electret filter. FPF showed the best performance than others, and the removal efficiencies were 89.5, 98.6, and 99.8% when the sodium chloride aerosol were sized in 100, 200, and 300 nm, respectively. In addition, FPF had almost no decrease in the removal efficiency after the treatment by isopropyl alcohol (IPA). On the other hand, the IPA-treated PS and electret filter showed the rapid decrease around 20-40% for the sodium chloride aerosol. The performance of FPF was also kept even after the water treatment. Furthermore, FPF also showed good antibacterial activity, a desirable characteristic for using the air filter without infections. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: HYDROGEN-CHLORIDE; AIR FILTRATION; PERFORMANCE; PARTICLES; NANOFIBERS; EFFICIENCY; CHARGE; PM2.5; POLYACRYLONITRILE; FABRICATION